Extensive peritoneal lavage with saline after curative gastrectomy for gastric cancer (EXPEL): a multicentre randomised controlled trial. (February 2021) - Yang, Han Kwang; Ji, Jiafu; Han, Sang Uk; Terashima, Masanori; Li, Guoxin; Kim, Hyung Ho; Law, Simon; Shabbir, Asim; Song, Kyo Young; Hyung, Woo Jin; Kosai, Nik Ritza; Kono, Koji; et al.
Summary: Background: Peritoneal recurrence of gastric cancer after curative surgical resection is common and portends a poor prognosis. Early studies suggest that extensive intraoperative peritoneal lavage (EIPL) might reduce the risk of peritoneal recurrence and improve survival. We aimed to evaluate the survival benefit of EIPL in patients with gastric cancer undergoing curative gastrectomy. Methods: In this open-label, phase 3, multicentre randomised trial, patients aged 21–80 years with cT3 or cT4 gastric cancer undergoing curative resection were enrolled at 22 centres from South Korea, China, Japan, Malaysia, Hong Kong, and Singapore. Patients were randomly assigned to receive surgery and EIPL (EIPL group) or surgery alone (standard surgery group) via a web-based programme in random permuted blocks in varying block sizes of four and six, assuming equal allocation between treatment groups. Randomisation was stratified according to study site and the sequence was generated using a computer program and concealed until the interventions were assigned. After surgery in the EIPL group, peritoneal lavage was done with 1 L of warm (42°C) normal 0·9% saline followed by complete aspiration; this procedure was repeated ten times. The primary endpoint was overall survival. All analyses were done assuming intention to treat. This trial is registered with ClinicalTrials.gov, NCT02140034 . Findings: Between Sept 16, 2012, and Aug 3, 2018, 800 patients were randomly assigned to the EIPL group (n=398) or the standard surgery group (n=402). Two patients in the EIPL group and one in the standard surgery group withdrew from the trial immediately after randomisation and were excluded from the intention-to-treat analysis. At the third interim analysis on Aug 28, 2019, the predictive probability of overall survival being significantly higher in the EIPL group was less than 0·5%; therefore, the trial was terminated on the basis of futility. With a median follow-up of 2·4 years (IQR 1·5–3·0), the two groups were similar in terms of overall survival (hazard ratio 1·09 [95% CI 0·78–1·52; p=0·62). 3-year overall survival was 77·0% (95% CI 71·4–81·6) for the EIPL group and 76·7% (71·0–81·5) for the standard surgery group. 60 adverse events were reported in the EIPL group and 41 were reported in the standard surgery group. The most common adverse events included anastomotic leak (ten [3%] of 346 patients in the EIPL group vs six [2%] of 362 patients in the standard surgery group), bleeding (six [2%] vs six [2%]), intra-abdominal abscess (four [1%] vs five [1%]), superficial wound infection (seven [2%] vs one [<1%]), and abnormal liver function (six [2%] vs one [<1%]). Ten of the reported adverse events (eight in the EIPL group and two in the standard surgery group) resulted in death. Interpretation: EIPL and surgery did not have a survival benefit compared with surgery alone and is not recommended for patients undergoing curative gastrectomy for gastric cancer. Funding: National Medical Research Council, Singapore.